The Relationship between Nurse Caring Behaviour and Nurse-Patient Interpersonal Relationship in the Inpatient Room - Anisah Ardiana; Alfid Tri Afandi; Dwi Nuria Arifin; Nurfika Asmaningrum; Kholid Rosyidi Muhammad Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The patient is the focus of nursing care, so interpersonal relationships between nurses and patients are needed. Caring behavior can create harmonious interpersonal relationships between nurses and patients. Nurses' caring behaviors are friendly and they always empathize with patients and their families. The study aimed to analyze the relationship between nurse caring behavior and nurse-patient interpersonal relationship in the inpatient room at RSU dr. H. KoesnadiBondowoso. The correlation method used was cross-sectional. The sampling technique applied total sampling with 104 nurses in the inpatient room. This study was analyzed using Kendall's tau-b because the two variables had ordinal scales. The results of Kendall's tau-b test showed that p-value = 0.025 (p less than 0.05) with a correlation coefficient of 0.221, which meant that the correlation of the two variables was positive as the strength of the relationship was weak. Nurses with caring behavior were 56 respondents (53.8%), and nurses with good nurse-patient interpersonal relationship quality were 62 (59.6%). This research is expected to be a policy framework for hospital management to improve quality services. Abstrak: Pasien merupakan fokus dari asuhan keperawatan, sehingga hubungan interpersonal yang baik antara perawat dengan pasien sangat dibutuhkan. Perilaku caring dapat memciptakan hubungan interpersonal yang harmonis antara perawat dengan pasien. Perilaku caring perawat meliputi sikap ramah dan selalu bersikap empati terhadap pasien dan keluarganya. Penelitian ini bertujuan untuk menganalisis hubungan antara perilaku caring perawat dengan kualitas hubungan interpersonal perawat-pasien di ruang rawat inap RSU dr. H. Koesnadi Bondowoso. Metode korelasi yang digunakan adalah cross sectional. Teknik pengambilan sampel menggunakan total sampling dengan 104 perawat di ruang rawat inap. Hasil uji Kendall’s tau-b menunjukkan bahwa p-value = 0,025 (p kurang dari 0,05) dengan koefisien korelasi sebesar 0,221 yang berarti korelasi kedua variabel tersebut positif dengan tingkat kekuatan hubungan yang lemah. Perawat dengan perilaku caring sebanyak 56 responden (53,8%) dan perawat yang memiliki kualitas hubungan interpersonal perawat-pasien yang baik sebanyak 62 responden (59,6%). Penelitian ini diharapkan dapat menjadi kerangka kebijakan bagi manajemen rumah sakit sebagai upaya peningkatan mutu pelayanan